Chemical constituents and medical benefits of plantago major - Adom, Muhammad Bahrain; Bakhtiar, M. Taher; Mutalabisin, Muhammad Fathiy; Amri, Mohamad Shahreen; Abdul Kudos, Muhammad Badri; Wan Sulaiman, Wan Azizi; Sengupta, Pinaki; Darnis, Deny Susanti (Elsevier Masson SAS, 2017)
The medicinal benefits of Plantago major have been acknowledged around the world for hundreds of years. This plant contains a number of effective chemical constituents including flavonoids, alkaloids, terpenoids, phenolic acid derivatives, iridoid glycosides, fatty acids, polysaccharides and vitamins which contribute to its exerting specific therapeutic effects. Correspondingly, studies have found that Plantago major is effective as a wound healer, as well as an antiulcerative, antidiabetic, antidiarrhoeal, anti-inflammatory, antinociceptive, antibacterial, and antiviral agent. It also combats fatigue and cancer, is an antioxidant and a free radical scavenger. This paper provides a review of the medicinal benefits and chemical constituents of Plantago major published in journals from year 1937 to 2015 which are available from PubMed, ScienceDirect and Google Scholar.